PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (STUDI KASUS: BANK UMUM SYARIAH PERIODE 2015-2020) - Yogie Febiwandio; Hesi Eka Puteri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The purpose of this study is to determine the influence of liquidity and solvency on the company's financial performance and company size as a control variable. The problem starts with the inconsistency of the results of previous research and the phenomenon that not all Islamic Commercial Banks have good financial performance. The research uses a quantitative method which collects and analyzes financial report data from the 2015-2020 period, where Islamic Commercial Banks are the object with a population of 14 and the sample meets the criteria for 8 Islamic Commercial Banks. The data sample is 192 data presented quarterly and after the Outlier test is carried out, the research data becomes 171 data. The results of the study show that each separate variable (partially) explains that the liquidity variable (FDR) does not have a positive and significant effect on ROE, but solvency has a positive and significant effect on ROE. Furthermore, together (simultaneously) the variable liquidity (FDR), solvency (DER) has a positive value and has a significant influence on ROE with firm size (LN Size) as the control variable. From the study of the results of this study, the novelty was obtained, namely financial distress (financial difficulties), in which conditions when Islamic Commercial Banks are unable to meet their needs and obligations due to inadequate finances. Moreover, in 2020 Indonesia is experiencing difficult conditions due to covid-19, if it does not rise and be overcome, this situation will lead to bankruptcy, especially Islamic Commercial Banks which always suffer losses and are unable to pay their obligations. The research results are expected to contribute positively to subsequent research as a comparison.Keywords: Liquidity, Solvency, Financial Performance, Company Size.